1992
DOI: 10.1121/1.402957
|View full text |Cite
|
Sign up to set email alerts
|

Detection of oscillatory and impulsive transients using higher-order correlations and spectra

Abstract: Higher-order cross and ordinary correlation detectors are applied to four deterministic transients contaminated by uncorrelated Gaussian noise only. Histograms and moments are used to examine the properties of the signals and their effect on detector performance. Receiver operating characteristic (ROC) curve analysis and limiting signal-to-noise ratios for ‘‘good’’ detection provide comparative measures for different detectors. Probability density functions of detection ordinate values of signal-present and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The bicorrelation and tricorrelation can also be formed using output from only two sensors and repeating signals in various ways (Pflug et al, 1992b(Pflug et al, , 1994.…”
Section: The Efficacy Of Higher-order Detectors Vis-h-vis the Ordi-mentioning
confidence: 99%
See 1 more Smart Citation
“…The bicorrelation and tricorrelation can also be formed using output from only two sensors and repeating signals in various ways (Pflug et al, 1992b(Pflug et al, , 1994.…”
Section: The Efficacy Of Higher-order Detectors Vis-h-vis the Ordi-mentioning
confidence: 99%
“…Previous studies by the authors have shown that the normalized third-and fourth-order signal moments are reliable indicators of higher-order correlation detector performance [Pflug et al (1992b)]. For a deterministic energy transient of known moments through fourth order, it is possible to predict theoretically the amount of gain over an ordinary cross-correlation detector for a bicorrelation or tricorrelation detector applied in a noise environment of known variance.…”
mentioning
confidence: 99%
“…In order not to miss a possibly valid TDOA measurement, the threshold of the transient detector [7] can be lowered, and, consequently, the probability of false alarm is increased. In this way, all sensor pairs that contain sensors with invalid data may not be eliminated, and, as a result, some TDOAs in the measurements batch Z may be erroneous (clutter).…”
Section: B Tdoa Measurementsmentioning
confidence: 99%
“…, R, and use them to compute TDOAs for the detected transients as follows. First, we attempt to identify the sensor pairs that have received replicas of the emitted transient and for this purpose we use the cross-correlationbased transient detectors described in [7]. These detectors apply ordinary and higher-order cross-correlations computed using the signals received by two or more different sensors.…”
Section: B Tdoa Measurementsmentioning
confidence: 99%
See 1 more Smart Citation